The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.29063/ajrh2016/v20i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differentials and Disease-Specific Cause of Infant Mortality: A Case Study in an Urban Hospital in Accra, Ghana

Abstract: Infant mortality is a major public health problem especially in developing countries. It is an indicator of quality of and accessibility to primary healthcare as well as the overall health status of a country. Understanding the risk factors for infant mortality is the first important step to reducing its incidence/prevalence. This study examined the prevalence and disease-specific causes of infant mortality in an urban hospital in Ghana and gender differences in the burden of infant mortality. Births and death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(11 reference statements)
2
0
0
Order By: Relevance
“…Table 1 's assessment of the association between demographic characteristics and diagnosis of death reveals that sex, marital status, and mother's age exhibit no significant association with the cause of a child's death, disagreeing with most studies conducted on a national scale [ 14 ]. However, sex, which was not significant in the diagnosis of death, agrees with Adam's [ 15 ] study conducted at 37 Military Hospital Ghana. Furthermore, the age of the child, birth type, and weight at birth were associated with the diagnosis of death, agreeing with other studies conducted in teaching hospitals in Ghana [ 11 , 16 ].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Table 1 's assessment of the association between demographic characteristics and diagnosis of death reveals that sex, marital status, and mother's age exhibit no significant association with the cause of a child's death, disagreeing with most studies conducted on a national scale [ 14 ]. However, sex, which was not significant in the diagnosis of death, agrees with Adam's [ 15 ] study conducted at 37 Military Hospital Ghana. Furthermore, the age of the child, birth type, and weight at birth were associated with the diagnosis of death, agreeing with other studies conducted in teaching hospitals in Ghana [ 11 , 16 ].…”
Section: Resultssupporting
confidence: 88%
“…The study's findings underscored acute respiratory distress as a prominent cause of death among under-five children, followed by premature births and sepsis, which is in agreement with the global burden of diseases [ 6 ] and other hospital-based studies [ 11 , 15 , 16 ]. Supporting these findings, a systematic review and meta-analysis conducted by Wong et al [ 17 ] revealed a 24% overall mortality rate in pediatrics related to acute respiratory distress syndrome (ARDS).…”
Section: Resultssupporting
confidence: 80%